Tourism development and ecological footprint indicators in island destinations: evidence from the members of the alliance of small island states - Rezapouraghdam, Hamed; Altun, Ozlem; Saydam, Mehmet Bahri; Erkut, Burak (Routledge Journals, Taylor & Francis Ltd, 2024)
Considering the crucial debates on sustainable development it is significant to understand the link between the development of tourism in small island countries and the ecological footprint. However, to date, little knowledge is available about the contribution of tourism to the EF of small island states. Therefore, the study aims to investigate the effects of international tourism, tourism revenues, total natural resource rents, urbanisation, energy intensity, and per capita gross domestic product (GDP) on ecological footprint among the Members of the Alliance of Small Island States (AOSIS). The results of our study provide new empirical results on the impact of tourism, economic growth, energy intensity, natural resource rents, and urbanisation on the ecological footprint of the 7 AOSIS member countries. Cross-sectional dependency and cointegration test results are positive for the variables of interest. Our estimates based on CCEMG and AMG regressions showed which factors contribute to environmental degradation at the AOSIS and country levels.
Keywords: AOSIS; small island countries; ecological footprint; tourism; GDP; natural resource rents